Highly Efficient Control System Enabling Robot Accuracy Improvement - Buschhaus, Arnd; Blank, Andreas; Ziegler, Christian; Franke, Jörg (5th CATS 2014 - CIRP Conference on Assembly Technologies and Systems, 2014)
The developed control system utilizes existing network technologies and uses data of sensor systems for continuous process monitoring to derive the robots actual state in course of its movement. In case of a high speed camera the image data is acquired by the control system via a first thread and subsequently the actual robot position is calculated based on this data. At the same time, for determining the robots target state, the system continuously requests the robots nominal position from the robot controller by utilizing a parallel second thread. The information describing the robots actual state is then compared with the sensor data for calculating offset values. These offset values are subsequently filtered and a correction value is calculated. In a third parallel thread new movement instructions are generated, considering the offset values as well as the robots target trajectory. Finally, for remote control of the robot, these movement instructions are transferred to the robot controller. (C) 2014 Elsevier B.V.
Keywords: Industrial Robot; Control System; Accuracy Improvement